Integrating SQ3R Strategies to Improve Mathematical Problem-Solving Capabilities in Material Triangles - Nurlaelasari, Eva; Sari, Nenden Mutiara; Wahidin, Wahidin; Akkapin, Supaphorn; Yaniawati, Poppy (UNNES JOURNAL, 2025)
Indonesian students often struggle with solving math problems, especially when it comes to geometry, like problems involving triangles. However, previous studies have mostly focused on SQ3R in reading comprehension or general mathematics learning, leaving a gap in its application to geometry-based problem-solving. This study aims to examine the effectiveness of integrating the SQ3R strategy to enhance students’ mathematical problem-solving abilities on triangle materials. The research used a quantitative-qualitative method with a quasi-experimental design, and included two groups: an experimental group and a control group. The students were from a seventh-grade class at SMP Negeri 4 Cimahi, and they were divided into the two groups based on purposeful selection. Data was gathered through problem-solving tests, classroom observations, and other records. The results showed that the group that used SQ3R improved much more in their problem-solving skills compared to the group that didn’t use it. The SQ3R method helped students break down problems, come up with plans, do calculations, and check their answers in a better way. This study highlights the need for active literacy-based strategies in mathematics instruction and suggests future research to explore the broader application of SQ3R in other mathematical topics and grade levels. Abstrak Keterampilan siswa Indonesia dalam pemecahan masalah matematika masih dianggap rendah, terutama dalam pelajaran geometri seperti segitiga. Namun, penelitian sebelumnya sebagian besar berfokus pada penerapan SQ3R dalam keterampilan membaca atau pembelajaran matematika secara umum, sehingga masih terdapat kesenjangan dalam penerapannya pada pemecahan masalah berbasis geometri. Penelitian ini bertujuan untuk menguji efektivitas integrasi strategi SQ3R dalam meningkatkan kemampuan pemecahan masalah matematis siswa pada materi segitiga. Penelitian ini mengambil pendekatan kuantitatif-kualitatif dan menerapkan metode kuasi eksperimen berjenis Non-equivalent Control Group Design. Sampel terdiri dari 72 siswa kelas VII di SMP Negeri 4 Cimahi yang dibagi menjadi kelompok eksperimen dan kontrol, keduanya dipilih secara purposif. Alat penelitian terdiri dari tes penyelesaian masalah, pengamatan, dan dokumentasi. Temuan penelitian menunjukkan peningkatan yang signifikan dalam kemampuan pemecahan masalah siswa pada kelompok eksperimen dibandingkan dengan kelompok kontrol. Strategi SQ3R terbukti berhasil mendukung siswa dalam memahami permasalahan, merancang solusi, melakukan perhitungan, dan memeriksa hasil secara terstruktur. Penelitian ini menegaskan pentingnya penerapan strategi berbasis literasi aktif dalam pembelajaran matematika serta merekomendasikan penelitian lanjutan untuk mengeksplorasi penerapan SQ3R pada topik matematika dan jenjang pendidikan lainnya.